Risk-benefit assessment of closed intra-abdominal drains after pancreatic surgery: a systematic review and meta-analysis assessing the current state of evidence - Diener, Markus K.; Tadjalli Mehr, Keyvan; Wente, Moritz N.; Kieser, Meinhard; Büchler, Markus W.; Seiler, Christoph (Langenbeck's archives of surgery, 2011)
This systematic review aims to analyse the risk-benefit association of (1) prophylactic drains and/or (2) the time of their removal after pancreatic resection.
Published: 21 October 2010
Errata vom 15. Juni 2011: The original version of this article unfortunately contained a mistake.One of the authors’ names was incorrectly captured. The author’s correct name is Keyvan Tadjalli-Mehr
Gesehen am 30.05.2022